Comprehensive Characterization of Nanotransfer Printing System for Organic Electronic Devices - Hui, Lok Shu (My University, 2019)
This thesis presents a universal transfer printing method to introduce a thin layer of interlayer nanoparticle material in the cathode-organic layer interface in organic device. The use of reverse micelles for making nanoparticles restricts the nanoparticles to be directly synthesized on the organic active layer , therefore a transfer printing method using graphene was derived and a characterization method was needed to detect the transfer of nanoparticles in the whole device system. Raman spectroscopy was found to be the best candidate in studying these organic systems. The oxidation behavior and interaction of CVD graphene on Cu with oxygen plasma and mild annealing was monitored closely by a detailed Raman trilogy studies. Raman results also show evidence of graphene oxide successfully transferred to the target organic layer. Raman spectroscopy was further explored to understand all material in the transferred system including the micelles, type of nanoparticles and the organic layer, which then provides valuable insights to the evolution of the different phases of nanoparticle material formed by the reverse micelles technique. Raman was also used to confirm the first-reported formation of the hot-topic perovskites materials in reverse micelles. An extended Raman technique, the unconventional inverted-TERS, was used to detect a monolayer of micelles which was otherwise impossible for a normal Raman setting. The underlying mechanisms of this technique with high-resolution were also proposed. In order to understand and explore the tunability of reverse micelles on nanoparticle synthesis, a study with the pervovskite material was performed. There were evidence of precursors interacting with the pyridine group in the micelles core, which affects nanoparticle formation. The size of nanoparticles is also found to be tunable by using micelles of different block lengths and different solvents. All these findings contribute to future optimization on the nanoparticles to be transfer printed into devices interlayer and ultimately to benefit on the improvement on organic photovoltaics.
Keywords: Raman; Graphene; Nanotransfer Printing; Nanoparticles; Organic Photovoltaics; Perovskites